2001
DOI: 10.1098/rspb.2001.1648
|View full text |Cite
|
Sign up to set email alerts
|

Male great tits eavesdrop on simulated male–to–male vocal interactions

Abstract: Animal communication generally occurs in the environment of a network of several potential signallers and receivers. Within a network environment, it is possible to gain relative information about conspeci¢cs by eavesdropping on signalling interactions. We presented male great tits with the opportunity to gain such information by simulating singing interactions using two loudspeakers. Interactions were presented so that relevant information was not available in the absolute singing behaviour of either individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(98 citation statements)
references
References 25 publications
4
93
1
Order By: Relevance
“…In fact song sparrows in our population approach the playback speaker more readily when they are type matched by it [18]. Furthermore, as a long-range signal, song type matching may be eavesdropped on by other males [32,33]. We have previously found that song sparrow males will increase aggression towards their aggressive neighbours [34,35], which would introduce a second layer of social cost of type matching: if a male type matches a neighbour instead of repertoire matching, the norm between established neighbours [36], he may deal with increased aggression from other rspb.royalsocietypublishing.org Proc R Soc B 280: 20122517 neighbours which in turn may be more costly to bluffers than truly aggressive signallers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact song sparrows in our population approach the playback speaker more readily when they are type matched by it [18]. Furthermore, as a long-range signal, song type matching may be eavesdropped on by other males [32,33]. We have previously found that song sparrow males will increase aggression towards their aggressive neighbours [34,35], which would introduce a second layer of social cost of type matching: if a male type matches a neighbour instead of repertoire matching, the norm between established neighbours [36], he may deal with increased aggression from other rspb.royalsocietypublishing.org Proc R Soc B 280: 20122517 neighbours which in turn may be more costly to bluffers than truly aggressive signallers.…”
Section: Discussionmentioning
confidence: 99%
“…Territorial intrusions and interactions were simulated by song broadcast via loudspeakers from portable computers using methods and equipment identical to those used by Peake et al (2001). As figure 1 shows, song from one male (A) was first broadcast from within the subject's territory, simulating a territorial intrusion by an individual unknown to the subject.…”
Section: Methodsmentioning
confidence: 99%
“…The four treatments were presented according to a balanced design in order to avoid differences in response due to time of day or location. We then assayed the information extracted by the subject from the two interactions, the one in which he took part and the one he heard, and hence the ability of males to combine information from two sources, by intruding upon the territory using a loudspeaker broadcasting the songs of male B as a 5 min naturalized loop (see Peake et al 2001). The response of subjects to the assay was measured as the total number of songs produced and the number of song types used, the two variables that had revealed differences in responses to interactions between unknown males .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…predators for which signals reveal the presence of prey [1,2]. Research has examined eavesdropping in several contexts, including bystanders observing male-male contests [3][4][5], female mate choice copying [6,7], and predator detection of male courtship signals [8][9][10]. One less-studied area is social facilitation of courtship arising as a consequence of eavesdropping [11,12].…”
Section: Introductionmentioning
confidence: 99%